2010
DOI: 10.3109/02713683.2010.506966
|View full text |Cite
|
Sign up to set email alerts
|

MRI in Diagnosis of Orbital Masses

Abstract: Diffusion-weighted MRI and proton magnetic resonance spectroscopy increased the accuracy of diagnosis of orbital masses through giving in vivo tissue characterization; with magnetic resonance spectroscopy being more accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…It is important to note that previous studies mainly included other benign and malignant orbital neoplastic lesions rather than inflammatory orbital lesions. [9][10][11][12][13][14][15] Sepahdari et al 10 reported that an ADC of less than 1.0 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting malignancy and Politi et al 11 indicated that a threshold of 0.775 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting orbital lymphoma. Therefore, their reported optimal ADC may be unfit for differentiating orbital lymphoma from benign OLPDs because these ADC values are higher than the ADCs of the majority of benign OLPDs found in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that previous studies mainly included other benign and malignant orbital neoplastic lesions rather than inflammatory orbital lesions. [9][10][11][12][13][14][15] Sepahdari et al 10 reported that an ADC of less than 1.0 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting malignancy and Politi et al 11 indicated that a threshold of 0.775 ϫ 10 Ϫ3 mm 2 /s was optimal for predicting orbital lymphoma. Therefore, their reported optimal ADC may be unfit for differentiating orbital lymphoma from benign OLPDs because these ADC values are higher than the ADCs of the majority of benign OLPDs found in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Recently, some researchers have reported quantitative DWI with ADC measurements to be potentially useful for discriminating orbital lymphoma from other orbital tumors. [9][10][11][12][13][14][15] However, these studies in-cluded other neoplastic and nonneoplastic lesions such as cavernous hemangiomas, neurogenic tumors, and metastases, and the value of DWI for discrimination of lymphoma and OLPDs remains unclear. The purpose of this study was to assess the value of MR imaging including DWI and contrast-enhanced MR imaging for the discrimination of primary orbital lymphoma from benign OLPDs.…”
mentioning
confidence: 99%
“…10 Several retrospective studies have characterized orbital masses with DWI, and some have attempted to determine optimal quantitative ADC thresholds and their sensitivity and specificity in distinguishing malignant from benign lesions. 1118 These studies have shown somewhat conflicting results and have been limited by single-institution designs and potential selection bias inherent to their patient populations. Specifically, some studies have suggested that a single ADC threshold can be both highly sensitive and specific for predicting malignancy, 16 whereas other results have contradicted this statement.…”
mentioning
confidence: 99%
“…Specifically, some studies have suggested that a single ADC threshold can be both highly sensitive and specific for predicting malignancy, 16 whereas other results have contradicted this statement. 11,14 …”
mentioning
confidence: 99%
“…Because of low index of suspicion, this type of tumour usually is misdiagnosed57 as in our case. While T1 and T2 weighted MRI images are routinely used to diagnose intraocular tumours, newer methods like magnetic resonance spectroscopy could be considered in atypical cases to provide in vivo metabolic information of the tumours; this procedure has been shown to be effective in differentiation between benign and malignant orbital lesions in 93.7% of cases 8. Although procedures like positron emission tomography fused with CT are capable to detect the physiologic activity of medium to large size malignant tumours, they have limited value in diagnosis of early stages 9.…”
Section: Discussionmentioning
confidence: 99%